Serological survey of viral hepatitis markers among newly diagnosed patients with HIV/AIDS in China. Issue 3 (24th September 2012) - Shen, YZ; Wang, ZY; Qi, TK; Jiang, XY; Song, W; Tang, Y; Wang, JR; Liu, L; Zhang, RF; Zheng, YF; Dai, ZS; Lu, HZ
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to determine the seroprevalence and epidemiological features of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection among patients newly diagnosed with HIV/AIDS in China. Methods Two thousand and forty patients newly diagnosed with HIV/AIDS from 10 provinces in China were selected during 2009 to 2010. Serum samples obtained from each individual were screened for HBV and HCV serum markers [HBV surface antigen (HBsAg), HBV surface antibody (HBsAb), HBV envelope antigen (HBeAg), HBV envelope antibody (HBeAb), HBV core antibody (HBcAb) and HCV antibody (HCVAb)]; liver function tests were also performed. Demographics and medical histories were collected. Results Of the 2040 patients, 741 (36.3%) were positive for at least one HBV and HCV serum marker; 300 (14.71%) were HCVAb positive, and 248 (12.16%) were isolated HCVAb positive; 222 (10.9%) were positive for HBsAg; 19 (0.93%) were positive for both HBsAg and HCVAb. The highest prevalence of HBsAg positivity was found in Guangxi (15.31%), followed by Guangdong (15.19%) and Shanghai (14.36%). The highest prevalence of HCVAb positivity was found in Xinjiang (43.18%), followed by Henan (39.06%) and Yunnan (27.36%). The proportion of patients with abnormal liver function in patients positive for HCVAb and/or HBsAg was significantly higher than that in those who were negative for both HCVAb and HBsAg (P < 0.001). Conclusions The seroprevalence of HBV and HCV among patients newly diagnosed with HIV/AIDS in China is high. HBsAg and HCVAb positivity prevalences were found to vary significantly in different provinces in China. Patients newly diagnosed with HIV/AIDS and coinfected with HBV and HCV are at higher risk of abnormal liver function. It is necessary to routinely screen for HBV and HCV infection among patients newly diagnosed with HIV/AIDS.